2019
DOI: 10.1111/bjd.17873
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of basal and cutaneous squamous cell carcinoma in the U.K. 2013–15: a cohort study

Abstract: Summary Background Basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC), together known as keratinocyte cancers (KCs), are the commonest cancer in white ethnic populations. Recent improvements to registry data collection in England has allowed more accurate analysis of the epidemiology of BCC and cSCC and for the first time we are able to provide an accurate (representative) tumour burden for KC in the U.K. Objectives To estimate the incidence of BCC and cSCC in the U.K. Methods A cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 32 publications
2
122
0
2
Order By: Relevance
“…In the UK, between 2013 and 2015, 62.7% of cSCC arose in men (median age 80 years). The mean annual percentage increase was 5% between 2013 and 2015 [25,26]. In Norway, age-adjusted incidence rates increased nine-fold in females and six-fold in males from 1963 to 2011, particularly in the age group 70e79 years [27].…”
Section: Epidemiologymentioning
confidence: 95%
“…In the UK, between 2013 and 2015, 62.7% of cSCC arose in men (median age 80 years). The mean annual percentage increase was 5% between 2013 and 2015 [25,26]. In Norway, age-adjusted incidence rates increased nine-fold in females and six-fold in males from 1963 to 2011, particularly in the age group 70e79 years [27].…”
Section: Epidemiologymentioning
confidence: 95%
“…Teledermatology (TD) is often used to review skin cancer referrals. [1][2][3][4] A Cochrane review found that TD and faceto-face (F2F) review of skin cancer referrals had high levels of agreement for management decisions. 5 We compared waiting times and patient experience of a TD model with conventional F2F clinics.…”
mentioning
confidence: 99%
“…The conflict between our results and previous report may be attributed to different incidences of BCC in races and skin types. In Taiwan, the incidence of BCC was 8.4 per 100 000 person‐years in 2015 compared to 285 per 100 000 person‐years in the United Kingdom and 226 per 100 000 person‐years in the United States . Moreover, among previous reported cases, many were diagnosed solely based on hematoxylin and eosin staining, CK19 positivity, or BerEP4 positivity .…”
Section: Discussionmentioning
confidence: 99%